2021
DOI: 10.1080/13218719.2021.1904450
|View full text |Cite
|
Sign up to set email alerts
|

Verdict spotting: investigating the effects of juror bias, evidence anchors and verdict system in jurors

Abstract: The Scottish verdict of not proven represents a second acquittal verdict which is not legally defined. Existing research into the influence of the not proven verdict on jury decision making is modest. The main aim of the current study was therefore to investigate the influence of verdict systems (two vs three) on juror decision making. The effect of pre-trial bias and evidence anchors on juror judgements were also examined. One-hundred and twenty-eight mock jurors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…a proven and not proven system; . The Scottish verdict system has been reformed several times before it assumed its current form (Barbato, 2004;Curley, Murray, et al, 2021;Duff, 2021;Walker, 1988). The not proven verdict became part of the Scottish legal system through a convoluted, and unplanned, route (Barbato, 2004;Curley, Murray, et al, 2021;Walker, 1988).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…a proven and not proven system; . The Scottish verdict system has been reformed several times before it assumed its current form (Barbato, 2004;Curley, Murray, et al, 2021;Duff, 2021;Walker, 1988). The not proven verdict became part of the Scottish legal system through a convoluted, and unplanned, route (Barbato, 2004;Curley, Murray, et al, 2021;Walker, 1988).…”
mentioning
confidence: 99%
“…A number of studies have empirically investigated the influence of a two-verdict system (guilty and not guilty) compared to a three-verdict system (guilty, not guilty and not proven) on trial outcomes (Curley, Murray, et al, 2021;Hope et al, 2008;Smithson et al, 2007). For example, Curley, Murray, et al (2021) found that the availability of the not proven verdict decreased the number of guilty verdicts by 38.1% and not guilty verdicts by 74.4%. This suggests that conviction rates could change significantly by moving from a three-verdict system to a two-verdict system.…”
mentioning
confidence: 99%
See 3 more Smart Citations